Active recharge biphasic stimulation for the intraoperative monopolar review in deep brain stimulation - Mampre, David; Kim, Min Jae; Oliver, Tucker; Sorrentino, Zachary; Chandra, Vyshak; Christie, Carlton; Zakare-Fagbamila, Rasheedat; Hilliard, Justin D.; Wong, Joshua K. (Frontiers in Human Neuroscience, 2024)
Introduction: Charge balancing is used in deep brain stimulation (DBS) to avoid net charge accumulation at the tissue-electrode interface that can result in neural damage. Charge balancing paradigms include passive recharge and active recharge. In passive recharge, each cathodic pulse is accompanied by a waiting period before the next stimulation, whereas active recharge uses energy to deliver symmetric anodic and cathodic stimulation pulses sequentially, producing a net zero charge. We sought to determine differences in stimulation induced side effect thresholds between active versus passive recharge during the intraoperative monopolar review. Methods: 65 consecutive patients undergoing DBS from 2021-2022 were retrospectively reviewed. Intraoperative monopolar review was performed with both active recharge and passive recharge for all included patients to determine side effect stimulation thresholds. 16 patients with 64 total DBS contacts met inclusion criteria for further analysis. Intraoperative monopolar review results were compared with the monopolar review from the first DBS programming visit.The mean intraoperative active recharge stimulation threshold was 4.1 mA, while the mean intraoperative passive recharge stimulation threshold was 3.9 mA, though this difference was not statistically significant on t-test (p=0.442). Mean stimulation threshold at clinic followup was 3.2 mA. In Pearson correlation, intraoperative passive recharge thresholds had stronger correlation with follow-up stimulation thresholds (Pearson r = 0.5281, p < 0.001) than intraoperative active recharge (Pearson r = 0.340, p = 0.018), however the difference between these correlations was not statistically significant on Fisher Z correlation test (p = 0.294). The mean difference between intraoperative passive recharge stimulation threshold and follow-up stimulation threshold was 0.8 mA, while the mean difference between intraoperative active recharge threshold and follow-up threshold was 1.2 mA. This difference was not statistically significant on a t-test (p=0.134). Conclusions: Both intraoperative active recharge and passive recharge stimulation were wellcorrelated with the monopolar review at the first programming visit. No statistically significant differences were observed suggesting that either passive or active recharge may be utilized intraoperatively.